The New Framework Maintenance Optimization Using Reliability Centered Maintenance-FMEA - Erni Krisnaningsih; Gunawan Kristiyanto; Saleh Dwiyatno; Dadi Cahyadi (International Journal of Industrial Engineering and Engineering Management, 2025)
PT XYZ-Banten is the largest power generation company in Southeast Asia with a total output power of 3400 MW. The production process at PLTU XYZ is a continuous process. Of the 6 pumping machines that operate, if one of the machines or equipment is damaged or fails, the entire process will be stopped. Boiler Feed Pump (BFP) is the pump machine with the highest damage rate, with a percentage of 60% of all pumps located at PT XYZ-Banten. This research aims to optimize maintenance to increase reliability and minimize downtime on the BFP pump. The stages of the research with maintenance analysis using the Reliability Centered Maintenance (RCM)-FMEA method to identify the causes of failure, the impact caused, the category of damage, and the actions to be taken. The results with the Reliability Centered Maintenance (RCM)-FMEA method show that the most critical component is ARV with its task selection Condition Derect (CD) and the maintenance interval period for each component, including ARV 73 hours, Pipe 334 Hours, Mechanical Seal 960 hours, and Scooptube 1080 hours. Finally, the proposed improvements with 5W + 1H for more reliable and efficient maintenance optimization.  Management implications are expected to help companies prevent machine failures and determine other factors that cause these failures.